THE INFLUENCE OF INTERNAL FACTORS ON JOB SATISFACTION IN HEALTHCARE SETTINGS - Moh Yusuf; Ratna Dwi Wulandari (Indonesian Journal of Health Administration, 2023)
Background: Job dissatisfaction in healthcare facilities can increase medical errors. In order to reduce the medical errors, hospitals must focus on employee job satisfaction. In this case, both stress and burnout can lower job satisfaction. Aims: This research was conducted to analyze the internal factors that affect the level of job satisfaction of employees in health facilities. Methods: The method applied is the PRISMA framework, which consists of five stages, namely eligibility criteria, information sources, study selection, data collection process, and data items. Results: Systematic review was done on 34 quantitative studies about the factors that influence job satisfaction. Based on the review, the internal factors known are demographic and personal factors. In this case, demographic factors mostly do not affect employee job satisfaction, one of which is salary. Meanwhile, the most researched personal factor and the biggest influence is burnout. Conclusion: Based on the systematic review, it is known that the internal factors affecting employees’ job satisfaction include demographic and personal factors. The demographic factor that has a significant effect is salary, while the most researched individual factor is burnout. Working in the health sector requires caution so as not to cause medical errors. Health workers who experience burnout are at risk of causing medical errors. For that we need a strategy to overcome burnout so as to increase job satisfaction. Keywords: burnout, healthcare, internal factor, job satisfaction, PRISMA